IMPLEMENTATION OF COOPERATIVE SCRIPT LEARNING STRATEGIES TO IMPROVE MATHEMATICS LEARNING ACTIVITIES AND OUTCOMES - Seldy Derudinansyah; Uus Kusdinar (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
The research is in the background of low learning activity and low learning outcomes for students for mathematics lessons. This research aims to increase mathematics learning activity and improve grade VIII B students of Junior High School (SMP) Muhammadiyah Sewon Bantul Yogyakarta used a cooperative script learning strategy. This research used Classroom Action Research (CAR) used by a cooperative script learning strategy, which lasted for two cycles. Data collection mathematics learning activities using observation sheets, mathematics learning activities, and interviews with research subjects. While the measurement of student mathematics learning outcomes using test instruments formative at every end of the cycle. Data analysis uses qualitative analysis and uses descriptive statistical analysis. Research results revealed that the cooperative script learning strategy improves student mathematics learning activities and improves grade VIII B students of SMP Muhammadiyah Sewon Bantul Yogyakarta.